Belajar Akuntansi Seru: Catat, Hitung, dan Pahami Pajak Untuk Remaja Di Yayasan Al-Ikhwaniyah - Yusuf Yusuf; Muhammad Ikhsan Febriyanto; Aerlangga Aerlangga (Jurnal Pengabdian Kepada Masyarakat Kalam, 2026)
Accounting and taxation are essential components of financial literacy; however, they are often perceived as complex and uninteresting by young people. This community service program aimed to improve basic accounting literacy and tax awareness among adolescents at Yayasan Al-Ikhwaniyah through an interactive and enjoyable learning approach. The program was implemented using an educational and participatory method that combined interactive lectures, group discussions, simulations, and hands-on practice. Participants were introduced to simple financial recording, including income and expense tracking, as well as basic concepts of taxation and its role in national development. The results indicated a noticeable improvement in participants’ understanding of basic accounting concepts and their awareness of the importance of taxes. In addition, the program fostered positive attitudes toward responsible financial behavior and early tax awareness. Overall, this community service activity demonstrates that contextual and engaging learning methods are effective in enhancing financial and tax literacy among adolescents and can serve as a foundation for developing responsible economic behavior in the future.